PENGARUH CORE STABILITY EXERCISE TERHADAP PENINGKATAN KEMAMPUAN FUNGSIONAL PADA PRALANSIA DENGAN NYERI PUNGGUNG BAWAH DI DESA PURWODADI SIMPANG TAHUN 2022 - Erna Sariana; Salsabila Rohadatul Aisy; Mohammad Ali (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2022)
ABSTRACT Background: Non-specific low back pain is a musculoskeletal complaint that often causes disruption of daily activities, thereby reducing productivity in someone who experiences it. Core Stability Exercise is an exercise to control motion and position from the trunk to the pelvis which is used to perform optimal movements with isometric contractions aimed at gaining stability. Objective: To determine the effect of Core Stability Exercise on functional ability in the elderly with low back pain. Methods: Pre-experimental research with one group pre and post-test approach. The sample in this study amounted to 15 people. Measurement of functional ability using the Oswestry Disability Index questionnaire. Results: The average functional ability before the intervention was 20.13 and after the intervention was 6.53. after the statistical test, the results obtained p-value = 0.000 which means that there is a significant difference between functional ability before and after the intervention. Conclusion: There is an effect of Core Stability Exercise on improving the functional ability of the pre-elderly with low back pain.